The Role of International Arbitration in Resolving Cross-Border Commercial Disputes (Law and Justice research journal, 2025)
International arbitration has become a crucial mechanism for resolving cross-border commercial disputes due to its neutrality, enforceability, and efficiency. This study examines the role of international arbitration in addressing disputes between parties from different jurisdictions. The research explores the advantages of arbitration over litigation, including confidentiality, party autonomy, and the enforceability of arbitral awards under the New York Convention. Using a qualitative approach, this study analyzes key arbitration institutions such as the ICC, SIAC, and LCIA, alongside relevant case studies. The findings indicate that arbitration provides a flexible and effective dispute resolution framework, reducing legal uncertainties and fostering international trade and investment. However, challenges remain, including cost concerns and potential inconsistencies in arbitral decisions. The study suggests that harmonizing arbitration rules and increasing transparency could further enhance the effectiveness of international arbitration in cross-border commercial disputes.